Insight and Perspective From the Past. Issue 2 (12th February 2023) - Foley, John T.; MacDonald, Lynn C.; Pratt, Erica
Abstract: In exploring older physical education textbooks there is a renewed appreciation for past leaders and their foresight in critical areas of our profession. While a number of ideas have been floating around in the physical education world that are thought of as new or improved concepts: Terms such as social emotional learning, physical literacy, mastery, the whole child, and along with the notion of the importance of quality teaching and assessment, appear in numerous publications and/or popular websites. However, looking back at old textbooks these ideas are not new but recycled and reused good ideas from long ago. It reminds us that much of what we believe about quality physical education is often rooted in other eras - that the past is still the present.